Aspects to be considered when making innovation out of promising research results in surface technology. (4th March 2019) - Leisner, P.; Johansson, E.
ABSTRACT: In the eyes of industrialists, scientists often exaggerate the economic potential of their findings. The industrialists know that developing a new technology to production is associated with uncertainty and risks. To elucidate the challenges faced by the surface treatment industry, this paper discusses aspects that should be considered when making innovation out of promising research results. The Technology Readiness Level (TRL) metric for assessing maturity of a technology is discussed and exemplified. Additional risks of fluid character such as legislation, price of raw material and customer expectations are also discussed. Even though, the subject is of general relevance, the present discussion refers to surface technology and examples are given from copper plating of printed circuit boards, and durable and cost-efficient coatings on electrical connectors.